Dinamika Kualitas Air dan Kepadatan Plankton Terhadap Pertumbuhan Ikan Nilem (Osteochilus vittatus) di Kolam Budidaya Desa Beji, Kedungbanteng, Banyumas - Astuti, Wahyu Widi; Sayidina, Aprilia; Sabrina, Aulia Putri; Widhi, Raut Nugrahening; Hidayati, Nuning Vita; Irawan, Hery; Samudra, Sesilia Rani (Fakultas Perikanan dan Ilmu Kelautan, 2025)
Water quality becomes an important parameter to observe in aquaculture activities to understand its impact on fish growth. The objective of this research is to determine the effect of plankton density and the parameters of pH, temperature, and dissolved oxygen on the growth of Nilem fish (Osteochilus vittatus). The research was conducted from September 2024 to October 2024. The method used is quantitative, which includes plankton density, Nilem fish weight, and water quality, with the results presented as numerical data in the form of tables and graphs. The average temperature of the Nile tilapia cultivation pond is 32°C, dissolved oxygen with an average value of 4.95, and pH with an average value of 6. The highest fish growth rate was in the first week at 8.39%, followed by the fourth week at 7.29%, while the growth rates in the second and third weeks did not reach 5%. The results of the plankton density regression analysis found that 6% of the specific growth rate is influenced by this factor, while 94% is influenced by other factors. The correlation coefficient (r) obtained is 0.24 and the value of b = -11.611x (negative relationship). Based on PP No. 22 of 2021, the water quality value of this nilem fish farming pond still meets the water quality standard, but compared to the water quality for nilem fish farming, the average water quality value measured in this farming pond does not meet the standard. The observed plankton density over 4 weeks showed fluctuating results, and the growth rate of Nile tilapia also exhibited fluctuating results. The relationship between plankton density and the growth rate of Nile tilapia is classified as weak.